Oil, debt, banking and the world recession - Ferdinand E. Banks (Intereconomics, 1983)
The threat of a major debt crisis is presently hanging over the international financial community like Damocles' sword. Behind the crisis lies the flood of petrodollars into the financial institutions of the industrial world since the mid 1970s and the consequent large-scale lending to “doubtful customers”. A simple solution to the problem is not in sight.
Keywords: 330; Oil Funds